Winter and Season-Only Irrigation with Late Summer Irrigation Termination Influences Alfalfa Dry Matter Yield and Applied Water Use Efficiency - Leonard M. Lauriault; Murali K. Darapuneni; Koffi Djaman; Mark A. Marsalis (Agriculture)
Increasing water scarcity for agricultural irrigation demands options to maximize yield with available water. Alfalfa (Medicago sativa) is a valuable crop in arid and semiarid regions and is considered a major user of irrigation water. Consequently, an area of established alfalfa was center-pivot-irrigated over two years according to one of four irrigation regimes, each with three replicates as strip plots. These were started after the last of the six harvests of the year, after seeding: winter-irrigated and throughout the growing season (winter full), winter-irrigated and terminated after the 4th harvest (winter limited), irrigated from mid-April, when canal water typically becomes available, and throughout the remainder of the growing season (season full), or typically-irrigated until the 4th harvest (season limited). Annual dry matter yield (DMY) was increased using winter irrigation compared to season-only irrigation (10.34, 8.94, 8.67, and 6.54 Mg ha−1 for winter full, winter limited, season full, and season limited, respectively, p < 0.0001, SEM 0.45). Irrigation termination after the fourth harvest with no winter irrigation significantly reduced annual applied water use efficiency (AAWUE) compared to all other treatments (9.08, 8.59, 8.82, and 7.38 kg DMY ha−1 mm−1 for winter full, winter limited, season full, and season limited, respectively; p < 0.0098, SEM = 0.38). Winter irrigation to fill the soil profile, followed by late summer irrigation termination, is feasible for increasing alfalfa productivity over season-only irrigation.